Cerebrospinal fluid leaks following intradural spinal surgery—Risk factors and clinical management - Lenschow, Moritz; Perrech, Moritz; Telentschak, Sergej; Von Spreckelsen, Niklas; Pieczewski, Julia; Goldbrunner, Roland; Neuschmelting, Volker (Frontiers in Surgery, 2022)
Background: Cerebrospinal fluid leakage (CSFL) following spinal durotomy can lead to severe sequelae. However, while several studies have investigated accidental spinal durotomies, the risk factors and influence of clinical management in planned durotomies remain unclear. Methods: We performed a retrospective analysis of all patients that underwent planned intradural spinal surgery at our institution between 2010 and 2020. Depending on the occurrence of a CSFL, patients were dichotomized and compared with respect to patient and case related variables as well as dural closure technique, epidural drainage placement and timing of mobilization. Results: A total of 351 patients were included. CSFL occurred in 4.8% of all cases. Surgical indication, tumor histology, location within the spine, previous intradural surgery and medical comorbidities were not associated with an increased risk of CSFL development (all p > 0.1). Age (Odds ratio [OR], 0.335 [95% Confidence interval [CI] 0.105 - 1.066]) and gender (OR, 0.350 [95% CI, 0.110 - 1.115]) were not independently associated with CSFL development. There was no significant association between CSFL development and the dural closure technique (p = 0.251), timing of mobilization (p = 0.332) or placement of an epidural drainage (p = 0.321). Conclusion: CSFL following planned durotomy pose a relevant and quantifiable complication risk of surgery that should be factored in during preoperative patient counseling. Our data could not demonstrate superiority of any particular dural closure technique but support the safety of both early mobilization within 24 hours postoperatively and epidural drainage with reduced or no force of suction.